2019
DOI: 10.1097/bpo.0000000000001037
|View full text |Cite
|
Sign up to set email alerts
|

MRI in Postreduction Evaluation of Developmental Dysplasia of the Hip: Our Experience

Abstract: On the basis of our experience, MRI is an excellent, safe and, reliable modality to confirm maintenance of adequate femoral head position and to evaluate soft tissue interposition. We agree that MRI is the gold standard to early depict dislocation after closed reduction of DDH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…The AI was measured on standard anteroposterior radiograph. Series MRI were performed before operation and regularly in follow-ups [19][20][21]. Cartilaginous acetabular index (CAI), cartilage coronal acetabular head index (CCAHI), and cartilage sagittal acetabular head index (CSAHI) were measured on the T1-W SE anatomic sequence in the coronal and sagittal planes that showed the largest diameter of the femoral head according to Douira's study [22].…”
Section: Image Measurementsmentioning
confidence: 99%
“…The AI was measured on standard anteroposterior radiograph. Series MRI were performed before operation and regularly in follow-ups [19][20][21]. Cartilaginous acetabular index (CAI), cartilage coronal acetabular head index (CCAHI), and cartilage sagittal acetabular head index (CSAHI) were measured on the T1-W SE anatomic sequence in the coronal and sagittal planes that showed the largest diameter of the femoral head according to Douira's study [22].…”
Section: Image Measurementsmentioning
confidence: 99%
“…With the rapid development of imaging technologies, MRI has been shown to be advantageous in the detection of bony structures as well as cartilaginous and soft-tissue structures. Although there are significant individual differences in the location and degree of acetabular dysplasia [11], MRI can provide superior soft tissue resolution in cross-sectional imaging profiles without ionizing radiation and has been advocated for the assessment of acetabular morphology and growth disturbance or deficiencies of the capital femoral epiphysis, the discrimination of ossified and unossified components, especially the identification of joint congruity and obstacles to prevent the reduction of hip dislocation, and the detection of unexpected complications after surgical reduction [12]. Benefit from MRI, it's convenient for clinicians, regardless of experience level, subspecialty, or geographic origin, to assess the quality of hip reduction and predict surgical reduction of avascular necrosis (AVN).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the more unstable the hip joint is, the higher the hip abduction angle required to preserve reduction. Although there is some controversy regarding the abduction angle of the hip after CR 14,19,21,22 as to the ideal amount of abduction, it has come to be accepted that reduced hips should be immobilized in < 55° to 60° of abduction in order to prevent potential compromise of the vascular supply to the proximal femoral epiphysis with resulting epiphyseal osteonecrosis. 13,21-23 On the other hand, some researchers think that in order to obtain a stable reduction, hip abduction angle can be increased without increasing the risk of AVN.…”
Section: Discussionmentioning
confidence: 99%
“…In the years following, this has been corroborated in more reports. Dibello et al 14 reviewed 25 patients with Graf’s type IV DDH (29 hips) who underwent CR and spica cast immobilization at a mean age of 3.4 months. They found that none of them developed AVN during follow-up, and they concluded that abduction angle should be < 70° in order to maintain the hip reduction and to preserve the femoral head perfusion, thus avoiding the risk of AVN.…”
Section: Discussionmentioning
confidence: 99%